Three‐dimensional reciprocal space mapping of diffuse scattering for the study of stacking faults in semipolar () GaN layers grown from the sidewall of an r‐patterned sapphire substrate. (25th September 2013) - Lazarev, Sergey; Bauer, Sondes; Meisch, Tobias; Bauer, Martin; Tischer, Ingo; Barchuk, Mykhailo; Thonke, Klaus; Holy, Vaclav; Scholz, Ferdinand; Baumbach, Tilo
<x xml:space="preserve">Abstract</x> Three‐dimensional reciprocal space mapping of semipolar (<inline-graphic xlink:href="ark:/27927/pgg3g3b7168" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) GaN grown on stripe‐patterned r‐plane (<inline-graphic xlink:href="ark:/27927/pgg3g3b715q" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) sapphire substrates is found to be a powerful and crucial method for the analysis of diffuse scattering originating from stacking faults that are diffracting in a noncoplanar geometry. Additionally, by measuring three‐dimensional reciprocal space maps (3D‐RSMs) of several reflections, the transmission electron microscopy visibility criteria could be confirmed. Furthermore, similar to cathodoluminescence, the 3D‐RSM method could be used in future as a reliable tool to distinguish clearly between the diffuse scattering signals coming from prismatic and from basal plane stacking faults and from partial dislocations in semipolar (<inline-graphic xlink:href="ark:/27927/pgg3g3b7168" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) GaN. The fitting of the diffuse scattering intensity profile along the stacking fault streaks with a simulation based on the Monte Carlo approach has delivered an accurate determination of the basal plane stacking fault density. A reduction of the stacking fault density due to the intercalation of an SiN interlayer in the GaN layer deposited on the sidewall of the pre‐patterned sapphire substrate has led to an improvement of the optoelectronic properties, influenced by the crystal quality, as has been demonstrated by a locally resolved cathodoluminescence investigation.